Introduction - Walker, Gustavo Fernández; Mora-Márquez, Ana María ; 0000-0002-9091-4863 (Argumentation Library, 2025)
This volume is one of the main outcomes of the 5-years research project The Medieval Reception of Aristotle’s Topics: A Pragmatic Account of Dialectical Argumentation? (henceforth Topica) The aim of the project was to study the medieval reception of Aristotle’s Topics, as the title indicates, and to produce critical editions of two of the main commentaries on the Topics from the thirteenth century: the question-commentary by the Parisian master of Arts Radulphus Brito, the last extant commentary of the century, and the literal commentary (possibly—the attribution is still to be confirmed) by the English Dominican Robert Kilwarby, which is the first extant commentary of the century (1230–40s?) and in all likelihood produced also at the Faculty of Arts of the University of Paris.
Publisher Copyright: © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.